Service-oriented computing : 15th International Conference, ICSOC 2017, Malaga, Spain, November 13-16, 2017, Proceedings /: 15th International Conference, ICSOC 2017, Malaga, Spain, November 13-16, 2017, Proceedings. (2017) - Unknown
No abstract available